(untitled) (Revista Latino-Americana de Enfermagem, 2011)
The aim of this study was to assess the level of agreement between an institutional protocol and the Manchester protocol for the risk assessment of patients attended in an emergency room of a public hospital in Belo Horizonte - MG - Brazil. This is a descriptive and comparative study, in which 382 patients' reports were evaluated and the risk was classified, using the institutional protocol and the Manchester protocol. Rates were calculated through weighted and unweighted kappa, in order to determine the level of agreement between the protocols. The results showed that the correlation between the protocols is average when considering that classification errors occurred between neighboring colors (kappa=0.48), and good when considering that classification errors occurred between extreme colors (kappa=0.61). The Manchester protocol increased the patients' level of priority of patients and has been considered more inclusive.